Toksoplasmosis Di Daerah Istimewa Yogyaicarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1989)
ABSTRAK Toxoplasmosis is a parasitic disease of man and animal caused by Toxoplasma gondii. The life cycle of this parasite consists of two phases. The reproductive phase, which takes place in the intestine of the cat, and the proliferative phase, which takes place in birds and mammalian species including humans. Toxoplasmosis is described as being either post-natal infection or transplacental intrauterine infection. This paper tries to report the insidental and the clinical manifestations of Toxoplasmosis retrospectifly. The report obtained from the resulcs of consultations and Toxoplasmosis serologycal examinations by using latex agglutination method during the year of 1987 through 1989 at the Laboratory of Parasitology, Faculty of Medicine, Gadjah Mada University. The incidence of Toxoplasmosis at Yogyakarta Special Region was 44,63%. Most of the cases were found between age of 10 to 39 years old. Men were more commonly infected with T. gondii than the women. Awide variety of clinical symptomps, was reported and the most commonly found was chorioretinitis.